Regulatory approval and a first‐in‐human phase I clinical trial of a monoclonal antibody produced in transgenic tobacco plants - Ma, Julian K‐C; Drossard, Jürgen; Lewis, David; Altmann, Friedrich; Boyle, Julia; Christou, Paul; Cole, Tom; Dale, Philip; van Dolleweerd, Craig J; Isitt, Valerie; Katinger, Dietmar; Lobedan, Martin; et al. (Plant biotechnology journal, 2015)
Although plant biotechnology has been widely investigated for the production of clinical‐grade monoclonal antibodies, no antibody products derived from transgenic plants have yet been approved by pharmaceutical regulators for clinical testing. In the Pharma‐Planta project, the HIV‐neutralizing human monoclonal antibody 2G12 was expressed in transgenic tobacco (Nicotiana tabacum). The scientific, technical and regulatory demands of good manufacturing practice (GMP) were addressed by comprehensive molecular characterization of the transgene locus, confirmation of genetic and phenotypic stability over several generations of transgenic plants, and by establishing standard operating procedures for the creation of a master seed bank, plant cultivation, harvest, initial processing, downstream processing and purification. The project developed specifications for the plant‐derived antibody (P2G12) as an active pharmaceutical ingredient (API) based on (i) the guidelines for the manufacture of monoclonal antibodies in cell culture systems; (ii) the draft European Medicines Agency Points to Consider document on quality requirements for APIs produced in transgenic plants; and (iii) de novo guidelines developed with European national regulators. From the resulting process, a GMP manufacturing authorization was issued by the competent authority in Germany for transgenic plant‐derived monoclonal antibodies for use in a phase I clinical evaluation. Following preclinical evaluation and ethical approval, a clinical trial application was accepted by the UK national pharmaceutical regulator. A first‐in‐human, double‐blind, placebo‐controlled, randomized, dose‐escalation phase I safety study of a single vaginal administration of P2G12 was carried out in healthy female subjects. The successful completion of the clinical trial marks a significant milestone in the commercial development of plant‐derived pharmaceutical proteins.